Evolutionary position of Peruvian land snails (Orthalicidae) among Stylommatophora (Mollusca: Gastropoda) - Ramirez, Jorge (2009)
The genera Bostryx and Scutalus (Orthalicidae: Bulimulinae) are endemics from South America. They are mainly distributed on the western slopes of the Peruvian Andes. The goal of the present work was to assess their evolutionary position among the stylommatophoran gastropods based on the 16S rRNA mitochondrial marker. Four sequences were obtained, and along with 28 sequences of other Stylommatophora retrieved from the GenBank, were aligned with ClustalX. The phylogenetic reconstruction was carried out using the methods of Neighbor-Joining, Maximum Parsimony, Maximum Likelihood and Bayesian inference. The multiple sequence alignment had 371 sites, with indels. The two genera of the family Orthalicidae for the first time included in a molecular phylogeny (Bostryx and Scutalus), formed a monophyletic group along with another member of the superfamily Orthalicoidea (Placostylus), result that is comparable with that obtained with nuclear markers. Their evolutionary relationship with other land snails is also discussed.